A SNP marker panel for identifying farmed Norwegian Atlantic salmon and quantifying introgression in wild Scottish populations - John Gilbey; Eef Cauwelier; James Sampayo; Eric Verspoor; David J. Morris (Conservation Genetics Resources, 2025)

The early marine distribution of Atlantic salmon in the North‐east Atlantic: A genetically informed stock‐specific synthesis - John Gilbey; Kjell Rong Utne; Vidar Wennevik; Alexander Christian Beck; Kyrre Kausrud; Kjetil Hindar; Carlos Garcia de Leaniz; Corrine Cherbonnel; Jamie Coughlan; Tom F. Cross; Eileen Dillane; Dennis Ensing; et al. (Fish and Fisheries, 2021)
The survival of Atlantic salmon ( Salmo salar) , an increasingly rare anadromous species, has declined dramatically during its marine phase, with disproportionate impacts on the poorly understood early post‐smolt period. Logistical constraints on collecting oceanic data to inform this issue pose a formidable obstacle. To advance understanding of post‐smolt distributional ecology in the North‐east Atlantic, a comprehensive analysis of existing information was undertaken. Data were synthesized from 385 marine cruises, 10,202 individual trawls, and 9,269 captured post‐smolts, spanning three decades and ~4.75 million km 2 of ocean, with 3,423 individuals genetically assigned to regional phylogeographic origin. The findings confirm major migrational post‐smolt aggregations on the continental shelf‐edge off Ireland, Scotland and Norway, and an important marine foraging area in the Norwegian Sea. Genetic analysis shows that aggregational stock composition does not simply reflect distance to natal rivers, with northern phylogeographic stock groups significantly under‐represented in sampled high‐seas aggregations. It identifies a key foraging habitat for southern European post‐smolts located in international waters immediately west of the Vøring Plateau escarpment, potentially exposing them to a high by‐catch mortality from extra‐territorial pelagic fisheries. Evidence of the differential distribution of regional stocks points to fundamental differences in their migration behaviours and may lead to inter‐stock variation in responses to environmental change and marine survival. The study shows that understanding of post‐smolt marine ecology, as regards to stock‐specific variations in habitat utilization, biological performance and exposure to mortality factors, can be significantly advanced by data integration across studies and exploiting genetic approaches.

Ice sheets and genetics: Insights into the phylogeography of Scottish Atlantic salmon, Salmo salar L. - Eef Cauwelier; Eric Verspoor; Mark W. Coulson; Anja Armstrong; David Knox; Lee Stradmeyer; Lucy M.I. Webster; John Gilbey (Journal of Biogeography, 2018)
Aim We constructed an independent phylogeographical hypothesis ( IPH ) for Atlantic salmon ( Salmo salar L.) in Scotland and adjacent northern England and tested if the distribution of contemporary microsatellite variation accorded with the IPH . Location NW Europe. Methods Knowledge of post‐Last Glacial Maximum ( LGM ) landscape development and salmon biology were used to define a temporal sequence of late Quaternary ecological niche models and, combined with the central‐marginal ( CM ) model of diversity evolution, to formulate an IPH . Observed microsatellite locus variation for salmon from 102 rivers in Scotland and northern England was tested for agreement with the IPH . Results The IPH postulated (1) initial colonization ( c. 17 ka bp ) of multiple isolated deglaciating coastal regions by long‐distance dispersal, predominantly from SW Europe via the Atlantic, (2) intra‐region colonization dominated by local range expansion, (3) differentiation by founder effects/genetic drift, in line with CM , until deglaciation complete and regions merged ( c . 10 ka bp ). IPH regions were weakly but significantly differentiated, showed broad agreement with genetically defined regions, and genetic diversity within them positively correlated with time post‐deglaciation, conforming to the CM model. The greatest differentiation was seen for the most recently diverged populations, with evidence that accumulating homoplastic mutations muted older regional phylogeographical signatures. Main conclusions Microsatellite differentiation in Scottish Atlantic salmon is significantly but weakly conditioned by post‐ LGM deglaciation, with a mosaic of regional groups and a temporal cascade of within‐region CM effects caused by local range expansion as patches became deglaciated. Colonization was predominantly or exclusively from the south‐western European LGM refugium. Accumulating homoplastic mutations have increasingly reduced regional differentiation.

Half a century of genetic interaction between farmed and wild Atlantic salmon: Status of knowledge and unanswered questions - Kevin A Glover; Monica F Solberg; Phil McGinnity; Kjetil Hindar; Eric Verspoor; Mark W Coulson; Michael M Hansen; Hitoshi Araki; Øystein Skaala; Terje Svåsand (Fish and Fisheries, 2017)
Atlantic salmon ( Salmo salar ) is one of the best researched fishes, and its aquaculture plays a global role in the blue revolution. However, since the 1970s, tens of millions of farmed salmon have escaped into the wild. We review current knowledge of genetic interactions and identify the unanswered questions. Native salmon populations are typically genetically distinct from each other and potentially locally adapted. Farmed salmon represent a limited number of wild source populations that have been exposed to ≥12 generations of domestication. Consequently, farmed and wild salmon differ in many traits including molecular‐genetic polymorphisms, growth, morphology, life history, behaviour, physiology and gene transcription. Field experiments have demonstrated that the offspring of farmed salmon display lower lifetime fitness in the wild than wild salmon and that following introgression, there is a reduced production of genetically wild salmon and, potentially, of total salmon production. It is a formidable task to estimate introgression of farmed salmon in wild populations where they are not exotic. New methods have revealed introgression in half of ~150 Norwegian populations, with point estimates as high as 47%, and an unweighted average of 6.4% across 109 populations. Outside Norway, introgression remains unquantified, and in all regions, biological changes and the mechanisms driving population‐specific impacts remain poorly documented. Nevertheless, existing knowledge shows that the long‐term consequences of introgression is expected to lead to changes in life‐history traits, reduced population productivity and decreased resilience to future challenges. Only a major reduction in the number of escapees and/or sterility of farmed salmon can eliminate further impacts.

Transatlantic secondary contact in Atlantic Salmon, comparing microsatellites, a single nucleotide polymorphism array and restriction‐site associated DNA sequencing for the resolution of complex spatial structure - Ian R. Bradbury; Lorraine C. Hamilton; Brian Dempson; Martha J. Robertson; Vincent Bourret; Louis Bernatchez; Eric Verspoor (Molecular Ecology, 2015)
Identification of discrete and unique assemblages of individuals or populations is central to the management of exploited species. Advances in population genomics provide new opportunities for re‐evaluating existing conservation units but comparisons among approaches remain rare. We compare the utility of RAD ‐seq, a single nucleotide polymorphism ( SNP ) array and a microsatellite panel to resolve spatial structuring under a scenario of possible trans‐Atlantic secondary contact in a threatened Atlantic Salmon, Salmo salar , population in southern Newfoundland. Bayesian clustering indentified two large groups subdividing the existing conservation unit and multivariate analyses indicated significant similarity in spatial structuring among the three data sets. mt DNA alleles diagnostic for European ancestry displayed increased frequency in southeastern Newfoundland and were correlated with spatial structure in all marker types. Evidence consistent with introgression among these two groups was present in both SNP data sets but not the microsatellite data. Asymmetry in the degree of introgression was also apparent in SNP data sets with evidence of gene flow towards the east or European type. This work highlights the utility of RAD ‐seq based approaches for the resolution of complex spatial patterns, resolves a region of trans‐Atlantic secondary contact in Atlantic Salmon in Newfoundland and demonstrates the utility of multiple marker comparisons in identifying dynamics of introgression.

SNP‐array reveals genome‐wide patterns of geographical and potential adaptive divergence across the natural range of A tlantic salmon ( S almo salar ) - Vincent Bourret; Matthew P. Kent; Craig R. Primmer; Anti Vasemägi; Sten Karlsson; Kjetil Hindar; Philip McGinnity; Eric Verspoor; Louis Bernatchez; Sigbjørn Lien (Molecular Ecology, 2013)
Atlantic salmon ( S almo salar ) is one of the most extensively studied fish species in the world due to its significance in aquaculture, fisheries and ongoing conservation efforts to protect declining populations. Yet, limited genomic resources have hampered our understanding of genetic architecture in the species and the genetic basis of adaptation to the wide range of natural and artificial environments it occupies. In this study, we describe the development of a medium‐density A tlantic salmon single nucleotide polymorphism ( SNP ) array based on expressed sequence tags ( EST s) and genomic sequencing. The array was used in the most extensive assessment of population genetic structure performed to date in this species. A total of 6176 informative SNP s were successfully genotyped in 38 anadromous and freshwater wild populations distributed across the species natural range. Principal component analysis clearly differentiated E uropean and N orth A merican populations, and within E urope, three major regional genetic groups were identified for the first time in a single analysis. We assessed the potential for the array to disentangle neutral and putative adaptive divergence of SNP allele frequencies across populations and among regional groups. In E urope, secondary contact zones were identified between major clusters where endogenous and exogenous barriers could be associated, rendering the interpretation of environmental influence on potentially adaptive divergence equivocal. A small number of markers highly divergent in allele frequencies (outliers) were observed between (multiple) freshwater and anadromous populations, between northern and southern latitudes, and when comparing B altic populations to all others. We also discuss the potential future applications of the SNP array for conservation, management and aquaculture.

Asymmetrical viability in backcrosses between highly divergent populations of Atlantic salmon (Salmo salar): implications for conservation - Eef Cauwelier; John Gilbey; Catherine S. Jones; Leslie R. Noble; Eric Verspoor (Conservation Genetics, 2012)

Asymmetric gene flow and the evolutionary maintenance of genetic diversity in small, peripheral Atlantic salmon populations - Sofía Consuegra; Eric Verspoor; David Knox; Carlos García de Leániz (Conservation Genetics, 2005)

Detection of an NAD+-dependent malic enzyme locus in the atlantic salmonSalmo salar and other salmonid fish - Eric Verspoor; William C. Jordan (Biochemical Genetics, 1994)

Description and genetics of glucose phosphate isomerase (GPI) and phosphoglucomutase (PGM) polymorphisms in Asellus aquaticus (L.) - Eric Verspoor (Biochemical Genetics, 1982)